Estimation of NOx emissions from the combustion chamber of heavy-duty gas turbines. Issue 1 (February 2021) - Zhao, Qiaonan; Wang, Guofeng; Zhang, Haonan; Xu, Youning; Yang, Shuo
Abstract: In order to study the estimation of NOx emission, numerical optimization and data fitting methods are used to study the NOx emission law of the combustion chamber of heavy-duty gas turbines. The inlet pressure Pin, air mass flow ma, and average temperature in the combustion zone Tpz are used for the fitting of NOx emission estimation formula under the multi-parameter impact. The results show that this is a fast and effective research method for the estimation of NOx emissions in the combustion chamber under the condition of ensuring the accuracy, which can obtain the NOx emission far below the average level under the condition of optimal inlet pressure.